أثر الاشتمال المالي في تحقيق المسؤولية الاجتماعية في ضوء الشفافية المالية في البنوك التجارية (Journal of Economics and Management Research, 2023)
تهدف الدراسة إلي معرفة دور أبعاد الاشتمال المالي في تحقيق المسؤولية الاجتماعية لعملاء بنك العربي الإسلامي في قطاع غزة في ضوء الشفافية المالية . من أهم النتائج التي توصلت إليها هي أن المتوسط الحسابي النسبي لجميع فقرات إستبانة "الاشتمال المالي" يساوي (67.6%)، وهذا يعني أن هناك موافقة بدرجة متوسطة من قبل أفراد العينة على فقرات الاشتمال المالي. لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (α≤ 0.05) في استجابات أفراد العينة تعزى لمتغير الجنس،المؤهل العلمي،سنوات الخدمة. The study aims to know the role of the dimensions of the financial inclusion in achieving the social responsibility of the customers of the Arab Islamic Bank in the Gaza Strip in the light of financial transparency. One of the most important results reached is that the relative arithmetic average of all the "financial inclusion" questionnaire is equal to (67.6%), and this means that there is an average approval by the sample members on the paragraphs of the financial inclusion. There are no statistically significant differences at the level of significance (α≤ 0.05) in the responses of the sample members attributed to the gender variable, the scientific qualification, years of service.